Visualization of Academic Quality Assurance Metamodel Through the Creation of Academic Quality Assurance Metamodel Information System - Mokhtar, Rashidah; Othman, Siti Hajar; Jaafar, Nur Huda; Mohamad Malom, Mardziyana; Ramlan, Rohaizan (Journal of Soft Computing and Data Mining, 2022)
Academic quality assurance metamodel information system (AQAMIS) is a mobile-web-friendly system designed to manage academic quality assurance (AQA) knowledge structure for higher education using the AQA metamodel structure. This research describes the development and functionality of AQAMIS, as well as how it visualizes the AQA metamodel on a system-based level. The AQAMIS system transformed the metamodel class diagram design into a user-friendly design, making it easier for any non-technical user to understand the metamodel design. The AQAMIS is composed of two major parts: the AQA metamodel and the knowledge repository system. The metamodel addresses the issue of managing knowledge for quality assurance in higher education. While the system resolves the issue of sharing best practices in higher education AQA. The AQAMIS system assists in ensuring that academic quality assurance systems are implemented more efficiently and effectively in higher learning institutions (HLIs). AQAMIS is also a one-stop center for respective users such as HLI top management, policymakers, auditors, and quality assurance personnel to access their expertise and share best practices in AQA endeavors.